Penerapan Pemberian Teknik Tripod Position terhadap Kenaikan Saturasi Oksigen pada Pasien PPOK di Ruang Rawat Inap - Transsel Tanto Nicro Gea; Novita Elisabeth Daeli; Novita Anggraini (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic respiratory disease that can be prevented and treated, characterized by persistent and progressive airflow limitation. This condition causes patients to experience shortness of breath and decreased oxygen saturation, therefore requiring non-pharmacological interventions, one of which is the application of the Tripod Position to help improve patient oxygenation. This study used a case study design involving the application of Tripod Position therapy in three respondents diagnosed with COPD. The intervention was carried out for three consecutive days, with oxygen saturation levels being monitored before and after each intervention. The results of the Tripod Position application indicated an improvement in oxygen saturation in all respondents. Respondent 1 experienced an increase in oxygen saturation by 3%, respondent 2 by 1%, and respondent 3 by 3%. Overall, the application of the Tripod Position showed a positive effect in gradually increasing oxygen saturation among COPD patients. These findings suggest that the Tripod Position can be used as an effective non-pharmacological intervention in nursing care for COPD patients. Therefore, the Tripod Position is recommended to be applied as a simple, practical, and supportive therapy to improve oxygen saturation and respiratory function in COPD patients.